Arterial Blood Gas–Guided Optimization of Mechanical Ventilation in Nursing Practice - Jamla Omar Hady, Ruwaidat Al-Ardh Hospital; Halimah Obaid Alradhady; Samiha Saeed Moshbab Alasmari; Munirah Aql Almutairi; Munirah Aql Almutairi; Safiah Mohammed Saghir Maghfuri; Itidal Mohammed Alnam; Mona Aqlaa Alenazi; Sharifa Ahmed Khormi; Taher Hassan Ali Sumaily; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Arterial blood gas (ABG) analysis is a cornerstone in managing mechanically ventilated patients, offering critical insights into oxygenation, ventilation, and acid–base balance. Nurses play a pivotal role in interpreting ABG results and adjusting ventilator settings to optimize patient outcomes. Aim: This study aims to highlight the significance of ABG-guided ventilator optimization within nursing practice and its impact on patient safety and clinical outcomes. Methods: A comprehensive review of physiological principles, ventilator parameters, and ABG interpretation was conducted, emphasizing evidence-based strategies for individualized ventilator adjustments. Special considerations for conditions such as COPD, ARDS, asthma, restrictive lung disease, and cardiogenic pulmonary edema were analyzed. Results: ABG-guided interventions enable precise ventilator adjustments, improving oxygenation and ventilation while minimizing complications like volutrauma, barotrauma, and oxygen toxicity. Disease-specific strategies, including low tidal volumes for ARDS and prolonged expiratory times for obstructive disorders, were identified as critical for safe ventilation. Conclusion: Integrating ABG analysis with ventilator management enhances patient safety, reduces complications, and supports individualized care. Interprofessional collaboration and continuous monitoring are essential for effective implementation.